Processos mercantis e privatizantes na universidade pública: o caso da pós-graduação lato sensu e da pesquisa-inovação - Ferro, André José Sanaiotti Grade (Universidade Federal de São Carlos, 2023)
The object of study for this doctoral research is the transformations undergone by public universities in light of the context of (neo)liberal state policies articulated with the logic of valorization, (re)production, and accumulation of capital. This work elucidates the ways in which commercial and privatizing processes are present and become naturalized within the public university. To apprehend and understand the object of study in its entirety, unveiling its contradictions and conflicts, we chose to conduct an analysis that dialectically articulates the theoretical-political reflection on commodification and privatization, combined with the documentary analysis (UFSCar Activity Report, Resolutions, among others) regarding the transformations of public universities and, at the same time, an empirical study to understand how commercial and privatizing processes are concretely realized in reality. We analyzed the way, the modus operandi, in which UFSCar has instituted a legal and institutional apparatus (Support Foundation, Innovation Agency, innovation scholarships and PIDICT scholarship, part of the payment of royalties to researchers, among others) to facilitate, promote, and encourage that activities related to research-innovation and specialization courses (extension) operate from the perspective of a market-privatist rationality. The study shows that these commercial and privatizing processes range from charging tuition fees in specialization courses to the development and commercialization of technological innovations (intellectual properties) for the market in search of royalties for the university. For this, the thesis was structured in four chapters: in the first, the relationship between science/technology and the logic of capital was problematized; in the second, the historical-political and economic process of the creation of UFSCar in the context of the civil-military dictatorship and (neo)liberal policies was emphasized; in the third, the issue of commodification of specialization courses was addressed; and in the fourth, the realization of commercial and privatizing processes in the research-innovation area was elucidated. Thus, the study proves relevant for (re)thinking the function that the public university is assuming in this context of (neo)liberal policies, considering that, in theory, the public university is not a company and, therefore, its function should not be to produce goods; on the contrary, we believe that its primary function is to promote teaching, research, and extension focused on meeting the public and collective interests of society/the common good and not the private/market interests.
Commercial and privatizing processes in the public university: the case of lato sensu postgraduate and research-innovation
Keywords: Universidade Pública; Privatização; Neoliberalismo; Public University; Privatization; Neoliberalism; CIENCIAS HUMANAS; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO